The promotion of critical thinking skills in the KSSR classrooms : a case study of selected primary school teachers - Wirawani binti Kamarulzaman (Kulliyyah of Education, International Islamic University Malaysia, 2017)
The Malaysia Ministry of Education (MOE) made a huge paradigm shift in 2011 by introducing a new curriculum, Primary School Standard curriculum/ Kurikulum Standard Sekolah Rendah (KSSR) to primary school level. Teaching of critical thinking skills is one of the attributes introduced in the new curriculum. Researches on KSSR were mainly focused on School- Based Assessment (SBA) which is the assessment method accompanying KSSR and none were found to explore how the curriculum may enhance critical thinking skills among students. Thus, the main aim of the case study is to explore the means teachers employed in KSSR to promote critical thinking among students. Six teachers were selected from a primary school from Gombak district as participants of the study. The mixed method research designs were used to study the phenomenon. Quantitative design was used to determine teachers' thinking styles where a measurement tool called MSG Thinking Style Inventory was administered to participants. Interviews were conducted with teachers to explore their understanding of critical thinking skills and its importance to students; their teaching approaches conducted in classrooms as well as the challenges they face in implementing KSSR in classrooms. Classroom observations were also done as a triangulation procedure to interview data in addition to investigating teachers' ways to monitor student metacognition and students' critical thinking dispositions. Hikmah checklist was also utilised as a data collection method during observation. Result from the inventory found that teachers preferred executive thinking style. Findings from interviews suggested that teachers were able to lay down a few definitions of critical thinking skills, and its importance. Teachers also utilised questioning teaching method and i-Think tools in their teaching approach. Observation data suggested that questioning method and class discussions were some of the ways to monitor student metacognitive skills. Students also displayed some critical thinking dispositions such as open-mindedness and communicative skills. Teachers felt that the large number of students per class, the increase content syllabus and the decrease time allocation for lessons were the challenges they faced in implementing KSSR in classrooms. Finally, a model for promoting critical thinking skills in classrooms is proposed as guidelines for teachers in addition to other recommendation for future research.